IL‐7 downregulates IL‐7Rα expression in human CD8 T cells by two independent mechanisms. Issue 2 (4th December 2012) - Ghazawi, Feras M; Faller, Elliott M; Sugden, Scott M; Kakal, Juzer A; MacPherson, Paul A
Abstract : Interleukin (IL)‐7 is an essential nonredundant cytokine, and throughout the lifespan of a T‐cell signaling via the IL‐7 receptor influences cell survival, proliferation and differentiation. It is therefore no surprise that expression of the IL‐7 receptor alpha‐chain (CD127) is tightly regulated. We have previously shown that IL‐7 downregulates expression of CD127 at the cell surface and now elucidate the kinetics of that suppression and demonstrate that IL‐7 downregulates CD127 transcripts and surface protein in primary human CD8 T cells by two separate pathways. We show that IL‐7 induces the initial reduction in cell‐surface CD127 protein independent of transcriptional suppression, which is delayed by 40–60 min. Although IL‐7‐mediated downregulation of CD127 transcripts is dependent on Janus kinase (JAK)/STAT5, the early downregulation of surface CD127 protein is independent of JAK activity. The data further illustrate that low levels of IL‐7 induce smaller and transient decreases in CD127 transcripts and surface protein, whereas higher concentrations induce more profound and sustained suppression. Such flexibility in receptor expression likely allows for fine‐tuned immune responses in human CD8 T cells in different microenvironments and in response to different immunological challenges.